2014
DOI: 10.1021/jp501344t
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Permittivity and Density of Molecular Liquids under High Pressure

Abstract: We collected and analyzed the density and permittivity of 57 nonpolar and dipolar molecular liquids at different temperatures (143 sets) and pressures (555 sets). No equation was found that could accurately predict the change to polar liquid permittivity by the change of its density in the range of the pressures and temperatures tested. Consequently, the influence of high hydrostatic pressure and temperature on liquid permittivity may be a more complicated process compared to density changes. The pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
(60 reference statements)
0
16
0
1
Order By: Relevance
“…Relative dielectric constants, ε r (relative to the permittivity of a vacuum, ε o ), as functions of temperature on a semilog scale. The equations to plot ε r for all components except DIPE are taken from Wohlfarth; data for DIPE are taken from Kiselev et al …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative dielectric constants, ε r (relative to the permittivity of a vacuum, ε o ), as functions of temperature on a semilog scale. The equations to plot ε r for all components except DIPE are taken from Wohlfarth; data for DIPE are taken from Kiselev et al …”
Section: Resultsmentioning
confidence: 99%
“…These observed trends can be explained through the component polarities, which are related to the intermolecular polar forces and solvation effects, both of which are important phenomena in the (water + alcohol + entrainer) systems investigated here. 17 The polarities of the components involved, in terms of their dielectric constants, 18,19 are shown in Figure 8 as functions of temperature. According to the like-dissolves-like rule, a solute (in this case the alcohol) will solvate more easily in a solvent (water or entrainer) of similar polarity.…”
Section: Effect Of Temperature On the Composition Ofmentioning
confidence: 99%
“… a ref . b ref . c ref . d ref . e ref . f ref . g ref . h ref . i ref . j ref . k ref . l ref . m ref . n ref . o ref . p ref . q ref . r ref . s ref . …”
Section: Data Sources and Results For Solvent Electrostrictionunclassified
“…The pressure-dependent permittivity data for several solvents, 2-butanone, dichloroethanes, benzonitrile, and nitromethane, were obtained from Kiselev et al and fitted again to quadratic expressions for ln ε­( P ) T , with r corr 2 ≥ 0.999, except for 1,1-dichloroethane, for which r corr 2 = 0.9981. Although these authors related the permittivities to the densities, they did not provide direct data for the latter; thus, these were obtained from other sources.…”
Section: Data Sources and Results For Solvent Electrostrictionmentioning
confidence: 99%
“…However, in contrast, we can study the effects of pressure over a wider range. The pressure dependence of the permittivity has been reported for various solvents such as water, 26 organic solvents, [27][28][29][30] and thallous halides. 31 We have previously reported that the fluorescence spectrum of a mechanochromic molecule shows a red-shift under high pressures because of the increase in the solvent polarity around the molecule.…”
Section: Introductionmentioning
confidence: 99%